"Built Environment Flood Resilience Capability Maturity Model". (2018) - Adeniyi, Onaopepo; Perera, Srinath; Ginige, Kanchana
Abstract: Capabilities are required for managing the impact of disasters on the built environment. These capabilities need to be continually improved and there should be a way of assessing them. This paper focuses on the development of a built environment flood resilience capability maturity model for micro, small and medium-sized enterprises (MSMEs). The study utilised the concept of capability maturity modelling to achieve its aim. The model developed identifies the built environment flood resilience capabilities of MSMEs. This was achieved by identifying relevant capabilities from the literature and mapping accordingly with maturity level characteristics prior to verification and refinement. This paper is limited to the development of the conceptual version of the model. The flood resilience capability maturity model is aimed at providing an assessment, improvement and benchmarking methodology for built environment flood resilience capabilities.